The spectrum of peri-ictal MRI changes; four illustrative cases. (August 2017) - Williams, Jennifer; Mullins, Gerard; Delanty, Norman; Bede, Peter; Doherty, Colin P.
Highlights: Seizures can cause acute neuroimaging abnormalities on diffusion, T2-weighted and FLAIR sequences in the peri-ictal period. Areas of signal abnormality reflect areas of restricted water diffusion due to seizure induced cytotoxic oedema. The mesial temporal lobe, hippocampus and corpus callosum are particularly susceptible. It is vital clinicians are aware that these abnormalities may occur in the acute peri-ictal period. Close clinical and neuroimaging follow up is important to monitor if lesions persist or leave longer lasting sequelae. Abstract: Purpose: Seizure induced neuronal hyperexcitability and increased unmet metabolic neuronal demand results in failure of the sodium/potassium ATP pump. Sodium and water accumulates intracellularly with cellular swelling and reduced extracellular volume demonstrating hyperintensity on DWI and reduced ADC. The aim of this study was to describe 4 clinical cases where we identified abnormalities in diffusion restriction in the acute peri-ictal period and followed them longitudinally. Methods: Patients were recruited from the emergency department, clinical consultation service and epilepsy monitoring unit of two tertiary referral centres. Patients underwent either 1.5T or 3.0T MRI with DWI, ADC, T2-weighted and post contrast studies during their acute admission and again after a period of follow up. Results: Four patients were identified as having visible diffusion restriction and reduced ADC in one or both hippocampi and the splenium of the corpus callosum. These lesions either completely resolved, showed interval improvement or demonstrated atrophy on follow up imaging. The two patients with persisting abnormalities had presented with status epilepticus. Conclusions: These acute ictal imaging changes give clinicians an important in-vivo look at the dynamic neuronal metabolic environment in the peri-ictal period. Areas that appear most susceptible include the mesial temporal structures and corpus callosum. Close imaging follow up to document resolution or evolution of long lasting sequelae is vital. There is no clear consensus as to why some patients develop ictal related imaging changes and others do not. Seizure length and time interval from ictus to scan appear to play a role but larger prospective studies are needed to confirm this.